PANCASILA STUDENT PROFILE AS AN EFFORT TO STRENGTHEN CHARACTER IN FACING AI IN THE ERA OF THE FOURTH INDUSTRIAL REVOLUTION (ERA 4.0) - Winulyo, Abdillah Rosyid (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Education in Indonesia aims to internalize the values of Pancasila in the pupils, becoming a shared responsibility between family, school, and society. This research highlights the important role of education in shaping the character of the student profile of Pancasila as the basic capital of the nation. The research focuses on the social changes that occurred in the era of the Fourth Industrial Revolution (Era 4.0), especially with the emergence of artificial intelligence (AI) technology and the use of AI Chat as a learning tool. Character education is necessary to give birth to a young generation that has the identity of a strong nation. However, the challenges of the 4.0 era, such as information openness and digital globalization, demand new approaches. Using AI Chat as a learning tool becomes a solution to shaping the Pancasila generation. The research explores the impact of student interaction with AI Chat technology on character aspects, such as independence, digital ethics, and communication skills. Pancasila's student profile is a guide in embedding character in accordance with the values of Pancasila. This research aims to provide a deep understanding of student interaction with AI Chat and explore the integration of this technology into the educational curriculum. Thus, it is expected that AI Chat technology not only provides knowledge, but also forms a positive character, laying the foundation for individual success in the era of the Fourth Industrial Revolution.